Small Extracellular Vesicles From Brown Adipose Tissue Mediate Exercise Cardioprotection. Issue 10 (7th April 2022) - Zhao, Hang; Chen, Xiyao; Hu, Guangyu; Li, Congye; Guo, Lanyan; Zhang, Ling; Sun, Fangfang; Xia, Yunlong; Yan, Wenjun; Cui, Ze; Guo, Yongzhen; Guo, Xiong; et al.
Abstract : Rationale: Long-term exercise provides reliable cardioprotection via mechanisms still incompletely understood. Although traditionally considered a thermogenic tissue, brown adipose tissue (BAT) communicates with remote organs (eg, the heart) through its endocrine function. BAT expands in response to exercise, but its involvement in exercise cardioprotection remains undefined. Objective: This study investigated whether small extracellular vesicles (sEVs) secreted by BAT and their contained microRNAs (miRNAs) regulate cardiomyocyte survival and participate in exercise cardioprotection in the context of myocardial ischemia/reperfusion (MI/R) injury. Methods and Results: Four weeks of exercise resulted in a significant BAT expansion in mice. Surgical BAT ablation before MI/R weakened the salutary effects of exercise. Adeno-associated virus 9 vectors carrying short hairpin RNA targeting Rab27a (a GTPase required for sEV secretion) or control viruses were injected in situ into the interscapular BAT. Exercise-mediated protection against MI/R injury was greatly attenuated in mice whose BAT sEV secretion was suppressed by Rab27a silencing. Intramyocardial injection of the BAT sEVs ameliorated MI/R injury, revealing the cardioprotective potential of BAT sEVs. Discovery-driven experiments identified miR-125b-5p, miR-128-3p, and miR-30d-5p (referred to as the BAT miRNAs) as essential BAT sEV components for mediating cardioprotection. BAT-specific inhibition of the BAT miRNAs prevented their upregulation in plasma sEVs and hearts of exercised mice and attenuated exercise cardioprotection. Mechanistically, the BAT miRNAs cooperatively suppressed the proapoptotic MAPK (mitogen-associated protein kinase) pathway by targeting a series of molecules (eg, Map3k5, Map2k7, and Map2k4 ) in the signaling cascade. Delivery of BAT sEVs into hearts or cardiomyocytes suppressed MI/R-related MAPK pathway activation, an effect that disappeared with the combined use of the BAT miRNA inhibitors. Conclusions: The sEVs secreted by BAT participate in exercise cardioprotection via delivering the cardioprotective miRNAs into the heart. These results provide novel insights into the mechanisms underlying the BAT-cardiomyocyte interaction and highlight BAT sEVs and their contained miRNAs as alternative candidates for exercise cardioprotection.